Enhanced therapeutic efficacy of nanocurcumin over free curcumin in the management of diabetes mellitus - Chauhan, Pratibha; Prasad, GBKS (PharmaNutrition, 2025)
Numerous scientific studies have revealed that curcumin is a pleiotropic molecule and influences multiple signaling pathways but is rapidly eliminated from the body due to its poor bioavailability. In the present study, nanocurcumin was synthesized and evaluated the therapeutic efficacy of nanocurcuminin comparison to those of free curcumin in human subjects with type II diabetes mellitus. Curcumin nanoparticles (NPs) have been synthesized then analyzed employing particle size analyzer and X-ray diffraction, while therapeutic efficacy of nanocurcumin has been assessed by evaluating blood glucose level (BGL), lipid profiles, as well as oxidative stress markers. This randomized trial included subjects (n = 60) with criteria of type II diabetes mellitus(T2DM). Subjects had been allocated randomly for receiving either curcumin or nanocurcumin capsules (1000 mg/day and 600 mg/day, accordingly) for 12 weeks. Nanocurcumin capsules' therapeutic function has been investigated by monitoring blood glucose, lipid profile, oxidative stress biomarkers, and glycosylated hemoglobin, along with DNA damage, prior to and after therapy. Particle size analysis indicated an average particle size of 78 nm of nanocurcumin. 'Nanocurcumin capsules' daily administration for 12 weeks drastically reduced BGLs. Compared to free curcumin, nanocurcumin exhibited a markedly enhanced antihyperglycemic effect. It could additionally preserve lipid homeostasis. Subject demonstrated improvements in enzymatic as well as non-enzymatic biochemical indicators of oxidative stress. When compared directly with free curcumin, nanocurcumin proved to be a more effective antioxidant, indicating enhanced bioavailability and efficacy in mitigating oxidative damage. Current research results demonstrated ‘Nanocurcumin capsules’ anti-hyperglycemic, anti-hyperlipidemic and anti-oxidative potential in subjects with diabetes mellitus (DM). Nanocurcumin therapeutic potential had been prominent than curcumin. [Display omitted] •‘Nanocurcumin capsules’ decreased blood glucose level significantly.•The subjects exhibited improvement in enzymatic and non-enzymatic biochemical markers of oxidative stress.•DNA damage was recovered after 12 weeks of Nanocurcumin therapy.•The therapeutic potential of nanocurcumin was prominent than those of curcumin alone.